Finite Element Analysis on Thermal Effect of the Vehicle Engine - M. M., Noor; T. T., Mon; K., Kadirgama; R. A., Bakar (2009)
Finite element method was employed to develop computational model to analyze the temperature distribution in the vehicle engine that utilized spark-ignition system for power generation. Computational domain consists of combustion chamber as major part and its surrounding components such as valves, and exhaust port and water jacket. Simplified 2-dimensional model was developed using general-purpose FE code. The element type was 2D element. Material properties were taken from FE package library. Heat convection due to the presence of water was defined by convection coefficient. Thermal load due to combustion was defined to all nodes of combustion chamber. The finite element models were analyzed using the thermal transient heat transfer analysis. The computed results were validated by comparing the maximum temperature at the piston surface with the published result. The results were found to be agreeable. The computed temperature gradient at the crucial parts were plotted and discussed. It was found that the critical component in thermal fatigue was the exhaust port near the cylinder head and the material used to construct the engine part strongly influences the temperature distribution in the engine.